Investigating wastewater generation and wastewater effluent treatment in the South African fruit & vegetable processing industry - Van Schalkwyk, Christiaan Jacobus (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScFoodSc)--Stellenbosch University, 2021.